17th Annual Convention for California Chapter #4 of the National Association of Postmasters - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the 17th annual Postmasters convention. Men, women and children stand outside the San Jose Civic Auditorium. Some are wearing distinctive buttons, ribbons and flowers. One little girl, seated on a man's lap at the center of the photograph, holds a gavel in her hand.